FEATURES OF DIAZO DYE PHOTODECOMPOSITION IN AQUEOUS SOLUTIONS CONTAINING ZINC, ALUMINUM AND ERBIUM SALTS - Evstropyev, K S; Maslennikov, S Y; Dukelskiy, K V; Kolobkova, E V; Nikonorov, N V; Boltenkov, I S; Evstropiev, S K (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2019)
Subject of research.The features of diazo dye Chicago Sky Blue 6B photodecomposition in aqueous solutions containing the salts of zinc, aluminum and erbium were studied. The paper presents the research of effect of the type and concentration of salts of these metals on the spectral properties of solutions and kinetic dependencies of the decomposition processes of a diazo dye under the action of UV radiation from DRT-240 high-pressure mercury lamp. Method. The methodology of the studies consisted in the sequential measurement of the absorption spectra of the solutions on a Perkin-Elmer Labda 650 spectrophotometer in the UV and visible parts of the spectrum after UV irradiation of various durations and analysis of the observed spectral changes. Main results. Based on the research carried out, it was shown that the absorption spectrum of the dye changes in the presence of metal salts in solutions and an additional maximum appears on the characteristic broad and intense absorption band of the dye in the visible part of the spectrum (λ = 540–680 nm). That fact suggests the behavior of dye molecular structuring. When metal salts are introduced into the solution, the mechanism of its decomposition under the action of UV radiation also changes significantly. In the presence of metal salts, along with a decrease in the intensity of the absorption band of the dye in the visible part of the spectrum, its substantial shift to the shortwave region is also observed. Studies of the dye decomposition kinetics under UV irradiation showed that the rate of the dye photodegradation sharply increases in the presence of metal nitrates in solutions. The introduction of zinc nitrate into the solution has particularly strong effect on the dye photodegradation in an aqueous solution. Practical relivance.The experimental results obtained can be used in the development of photochemical processes for the purification of water from organic pollutants.